Biallelic deep intronic variant c.5457+81T>A in TRIP11 causes loss of function and results in achondrogenesis 1A - Upadhyai, Priyanka; Radhakrishnan, Periyasamy; Guleria, Vishal S.; Kausthubham, Neethukrishna; Nayak, Shalini S.; Superti‐Furga, Andrea; Girisha, Katta M. (Human mutation, 2021)
Biallelic loss of function variants in TRIP11 encoding for the Golgi microtubule‐associated protein 210 (GMAP‐210) causes the lethal chondrodysplasia achondrogenesis type 1A (ACG1A). Loss of TRIP11 activity has been shown to impair Golgi structure, vesicular transport, and results in loss of IFT20 anchorage to the Golgi that is vital for ciliary trafficking and ciliogenesis. Here, we report four fetuses, two each from two families, who were ascertained antenatally with ACG1A. Affected fetuses in both families are homozygous for the deep intronic TRIP11 variant, c.5457+81T>A, which was found in a shared region of homozygosity. This variant was found to cause aberrant transcript splicing and the retention of 77 base pairs of intron 18. The TRIP11 messenger RNA and protein levels were drastically reduced in fibroblast cells derived from one of the affected fetuses. Using immunofluorescence we also detected highly compacted Golgi apparatus in affected fibroblasts. Further, we observed a significant reduction in the frequency of ciliated cells and in the length of primary cilia in subject‐derived cell lines, not reported so far in patient cells with TRIP11 null or hypomorphic variants. Our findings illustrate how pathogenic variants in intronic regions of TRIP11 can impact transcript splicing, expression, and activity, resulting in ACG1A. We report four fetuses, two each from two families, ascertained antenatally with achondrogenesis (ACG1A) and homozygous for the deep intronic TRIP11 variant, c.5457+81T>A. This variant causes aberrant TRIP11 mRNA splicing resulting in retention of 77 base‐pairs of intron 18 and a drastic reduction of mRNA and protein levels. Abolished TRIP11 function resulted in highly compacted Golgi apparatus, severe reduction in the number of ciliated cells and the length of primary cilia.